Calypso: Effecting Conflict Transformation Through the Indigenous Calypso Art-Form - Edward M. Phillips (Journal of Global Initiatives, 2013)
The calypso, which forms an integral part of the carnival celebrations of the Republic of Trinidad and Tobago, is a syncretic popular art-form that has its origin in Africa. The art-form, having been influenced and adapted by the experiences of enslaved Africans in the Diaspora, has been fused in the vortex of plantation society. Today, the music of carnival has evolved considerably, with the calypso becoming one of the cornerstones of the carnival celebration. This paper looks at aspects of the subset of political calypsos that offer commentary on the socio-political and/or economic issues in the Republic of Trinidad and Tobago (Trinbago). It recognizes these calypsos as bedded in the popular practice of ritual resistance. In doing so this paper fuses the very diverse fields of ritual communication and "Conflict Transformation" with "Trinbago" history and culture. Hence, this text is not steeped in the ideological paradigm of a single academic discipline. The very nature of this work requires that it encompasses the dynamic interplay between popular art, music, language, calypso, and an understanding of the approaches and methods of Conflict Transformation, establishing a symmetrical balance between all of these fields. This article recognises the pre-existing forma/ and informal modes of dispute resolution. In extending on that duality, it adds a third non-formal cultural model of community conflict management which embodies the process of Conflict Transformation as described by Bush and Folger ( 1994), as this is applicable to Trinidad and Tobago's local, temporal context. By adding this new set of intellectual tools, this paper enables the recognition of the language of the political calypso as Symbolic Action (Burke, 1966) in a process of Conflict Transformation.